Bailing Out the World's Poorest - Ravallion, Martin (2012)
The current financial crisis is global in nature, but it will have differing impacts within the developing world. Some people and some countries are more vulnerable than others. The author believes that it also threatens to have lasting impacts for some of those affected, notably through the nutrition and schooling of children in poor families. The author believes mistakes were made in past crises and identifies key design features for safety net programs that can help compensate for the likely welfare losses in the short-term while also promoting longer-term recovery.